Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Sure, let's solve the problem step by step:
Given the values:
[tex]\[ x = \frac{3}{7} \][/tex]
[tex]\[ y = \frac{1}{3} \][/tex]
[tex]\[ z = 3 \frac{6}{7} \][/tex]
First, let's convert the mixed number [tex]\( z \)[/tex] into an improper fraction.
The mixed number [tex]\( 3 \frac{6}{7} \)[/tex] can be converted as follows:
[tex]\[ z = 3 \frac{6}{7} = 3 + \frac{6}{7} \][/tex]
Next, we convert [tex]\( 3 \)[/tex] into a fraction with the same denominator as [tex]\( \frac{6}{7} \)[/tex]:
[tex]\[ 3 = \frac{21}{7} \][/tex]
Now, let's add these fractions:
[tex]\[ z = \frac{21}{7} + \frac{6}{7} = \frac{21 + 6}{7} = \frac{27}{7} \][/tex]
Therefore, [tex]\( z \)[/tex] in improper fraction form is:
[tex]\[ z = \frac{27}{7} \][/tex]
Now, we need to calculate [tex]\( z + x \times y \)[/tex]. First, let's find [tex]\( x \times y \)[/tex]:
[tex]\[ x \times y = \frac{3}{7} \times \frac{1}{3} \][/tex]
[tex]\[ x \times y = \frac{3 \times 1}{7 \times 3} = \frac{3}{21} = \frac{1}{7} \][/tex]
Next, we add this product to [tex]\( z \)[/tex]:
[tex]\[ z + x \times y = z + \frac{1}{7} \][/tex]
Since [tex]\( z \)[/tex] is [tex]\( \frac{27}{7} \)[/tex] and [tex]\( x \times y \)[/tex] is [tex]\( \frac{1}{7} \)[/tex], we can write:
[tex]\[ z + x \times y = \frac{27}{7} + \frac{1}{7} \][/tex]
To add these fractions, we sum their numerators:
[tex]\[ z + x \times y = \frac{27 + 1}{7} = \frac{28}{7} \][/tex]
Finally, simplify the fraction:
[tex]\[ \frac{28}{7} = 4 \][/tex]
Thus, the value of [tex]\( z + x \times y \)[/tex] is:
[tex]\[ \boxed{4} \][/tex]
Given the values:
[tex]\[ x = \frac{3}{7} \][/tex]
[tex]\[ y = \frac{1}{3} \][/tex]
[tex]\[ z = 3 \frac{6}{7} \][/tex]
First, let's convert the mixed number [tex]\( z \)[/tex] into an improper fraction.
The mixed number [tex]\( 3 \frac{6}{7} \)[/tex] can be converted as follows:
[tex]\[ z = 3 \frac{6}{7} = 3 + \frac{6}{7} \][/tex]
Next, we convert [tex]\( 3 \)[/tex] into a fraction with the same denominator as [tex]\( \frac{6}{7} \)[/tex]:
[tex]\[ 3 = \frac{21}{7} \][/tex]
Now, let's add these fractions:
[tex]\[ z = \frac{21}{7} + \frac{6}{7} = \frac{21 + 6}{7} = \frac{27}{7} \][/tex]
Therefore, [tex]\( z \)[/tex] in improper fraction form is:
[tex]\[ z = \frac{27}{7} \][/tex]
Now, we need to calculate [tex]\( z + x \times y \)[/tex]. First, let's find [tex]\( x \times y \)[/tex]:
[tex]\[ x \times y = \frac{3}{7} \times \frac{1}{3} \][/tex]
[tex]\[ x \times y = \frac{3 \times 1}{7 \times 3} = \frac{3}{21} = \frac{1}{7} \][/tex]
Next, we add this product to [tex]\( z \)[/tex]:
[tex]\[ z + x \times y = z + \frac{1}{7} \][/tex]
Since [tex]\( z \)[/tex] is [tex]\( \frac{27}{7} \)[/tex] and [tex]\( x \times y \)[/tex] is [tex]\( \frac{1}{7} \)[/tex], we can write:
[tex]\[ z + x \times y = \frac{27}{7} + \frac{1}{7} \][/tex]
To add these fractions, we sum their numerators:
[tex]\[ z + x \times y = \frac{27 + 1}{7} = \frac{28}{7} \][/tex]
Finally, simplify the fraction:
[tex]\[ \frac{28}{7} = 4 \][/tex]
Thus, the value of [tex]\( z + x \times y \)[/tex] is:
[tex]\[ \boxed{4} \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.